Chemogenetic regulation of the TARP-lipid interaction mimics LTP and reversibly modifies behavior - Joongkyu Park; Coralie Berthoux; Erika Hoyos-Ramirez; Lili Shan; Megumi Morimoto-Tomita; Yixiang Wang; Pablo E. Castillo; Susumu Tomita (Cell Reports, 2023)
Summary: Long-term potentiation (LTP), a well-characterized form of synaptic plasticity, is believed to underlie memory formation. Hebbian, postsynaptically expressed LTP requires TARPγ-8 phosphorylation for synaptic insertion of AMPA receptors (AMPARs). However, it is unknown whether TARP-mediated AMPAR insertion alone is sufficient to modify behavior. Here, we report the development of a chemogenetic tool, ExSYTE (Excitatory SYnaptic Transmission modulator by Engineered TARPγ-8), to mimic the cytoplasmic interaction of TARP with the plasma membrane in a doxycycline-dependent manner. We use this tool to examine the specific role of synaptic AMPAR potentiation in amygdala neurons that are activated by fear conditioning. Selective expression of active ExSYTE in these neurons potentiates AMPAR-mediated synaptic transmission in a doxycycline-dependent manner, occludes synaptically induced LTP, and mimics freezing triggered by cued fear conditioning. Thus, chemogenetic controlling of the TARP-membrane interaction is sufficient for LTP-like synaptic AMPAR insertion, which mimics fear conditioning.